2016
DOI: 10.9778/cmajo.20150063
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in ankyloglossia and frenotomy in British Columbia, Canada, 2004-2013: a population-based study

Abstract: Large temporal increases and substantial spatial variations in ankyloglossia and frenotomy rates were observed that may indicate a diagnostic suspicion bias and increasing use of a potentially unnecessary surgical procedure among infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
63
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 17 publications
5
63
1
3
Order By: Relevance
“…Our results indicate that frenotomy rates in most of Australia have increased significantly over the past decade. Increases have similarly been reported for British Columbia in Canada (2004–2013: 89% increase) and the United States (1997–2012: 866% increase) 3 , 4 . Medicare data underestimate the frenotomy rate, as this information does not capture frenotomies in public hospitals, where Medicare rebates are usually not applied.…”
Section: Boxmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results indicate that frenotomy rates in most of Australia have increased significantly over the past decade. Increases have similarly been reported for British Columbia in Canada (2004–2013: 89% increase) and the United States (1997–2012: 866% increase) 3 , 4 . Medicare data underestimate the frenotomy rate, as this information does not capture frenotomies in public hospitals, where Medicare rebates are usually not applied.…”
Section: Boxmentioning
confidence: 85%
“…A range of techniques are employed to treat clinically significant ties surgically (frenotomy or frenectomy), including scissors and laser surgery. Increases in the number of tongue‐tie diagnoses and in lingual frenotomy rates have recently been reported in Canada and the United States 3 , 4 …”
Section: Boxmentioning
confidence: 99%
“…In the United States and Canada, a huge increase in the frequency of frenectomies was observed in recent decades and it has been suggested that this may be due to diagnostic suspicion bias owing to increased focus on breastfeeding initiation before hospital discharge. 27,28 Unnecessary frenectomies, besides placing an economic burden on families and healthcare systems, can also harm the children themselves. Complications reported include bleeding, recurrence, lip injury, injury to the Wharton ducts, infection, lingual dysfunction, and air-way compromise.…”
mentioning
confidence: 99%
“…Ankyloglossia in newborns with breastfeeding difficulties has been diagnosed and treated in North America with increasing frequency over the past ten years 1 , 2 . Kapoor and colleagues 3 report in this issue of the MJA that frenotomy rates in Australia increased by 420% between 2006 and 2016, with differences between states and territories in the magnitude of the change.…”
mentioning
confidence: 99%
“…Confusing, low quality, and sometimes misleading information propagated by social media and in online resources about ankyloglossia and its effect on breastfeeding possibly also increase the demand for treatment. Personal, societal and cultural expectations of the breastfeeding process are also likely to play roles; ankyloglossia is diagnosed more frequently in first‐born infants and in infants from families of higher socio‐economic status 1 , 2 …”
mentioning
confidence: 99%